Determinants of Euro Term Structure of Credit Spreads - Astrid Van Landschoot (National Bank of Belgium, 2004)
In this paper, we analyze wether the sensitivity of credit spread changes to financial and macroeconomic variables depends on bond characteristics such as rating and maturity. First, we estimate the term structure of credit spreads for different rating categories by applying an extension of the Nelson-Siegel method. Then, we analyse the determinants of credit spread changes. According to the structural models and empirical evidence on credit spreads, our results indicate that changes in the level and the slope of the default-free term structure, the market return, implied volatility, and liquidity risk significantly influence credit spread changes. The effect of these factors strongly depends on bond characteristics, especially the rating and to a lesser extent the maturity.
Keywords: C22; G15; 330; credit risk; structural models; Nelson-Siegel; Kreditrisiko; Zinsstruktur; Unternehmensanleihe; Theorie; Euromarkt; EU-Staaten